GEOLOGY OF PETERMANN ISLAND (WILHELM ARCHIPELAGO, WEST ANTARCTICA) - Mitrokhin, O.; Bakhmutov, V.; Gavryliv, L.; Аleksieienko A. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Petermann Island belongs to the Wilhelm Archipelago – a large island arc near the west coast of the Antarctic Peninsula in the area of the Ukrainian Antarctic Station "Akademik Vernadsky". All the principal petrographic units of the Andean gabbro-granite Intrusive Suite which belong to the Antarctic Peninsula Batholith, outcrop on the island. Similar to several other Meso- Cenozoic orogenic intrusions, which form a large magmatic belt of West Antarctica, the rocks of Petermann Island underwent metamorphism of different type and intensity. The authors examined geological setting of the Petermann Island and acquired principally new data on the spatial localization, structural measurements, age relations, petrographic features and chemical composition of separate intrusive bodies. The aim of the research was to reveal the geological sequence of magmatic intrusions and metamorphism of the intrusive bodies of Petermann Island. Geological fieldworks, followed by mineralogical and petrographic investigations prove that gabbroids and granitoids formed as a result of two different stages of magmatic activity, delimited by the intrusion of pre-granite basic dikes and subsequent regional metamorphism. Accordingly, the intrusive suites of Petermann Island cannot be a part of one magmatic complex (Andean Intrusive Suite or Antarctic Peninsula Batholith), as it was considered by the previous researchers of the area. The paper indicates that the most ancient intrusive-magmatic formations of Petermann Island are represented by the layered gabbroid intrusion. Only a fragment of the latter one outcrops on the northern shore of the island, while the biggest part of the intrusion being located under the sea level to the north and east. At least two groups of dikes are identified among the basic dikes of Petermann Island based on the age of their intrusion. Petrographic features of pre-granite gabbro-porphyrite dikes indicate hypabyssal level of their intrusion, unlike the plutonic level of the enclosing gabbroids. It is pointed out that the gabbroids and pre-granite dikes were significantly altered by regional metamorphism under amphibolite facies conditions prior to the intrusion of granitoids. The development of the superimposed actinolite-epidote-chlorite mineralization is associated either with the contact metamorphism induced by the intrusion of granitoids or with later fracture-controlled hydrothermal flow and metasomatism that occurred after the intrusion of granitoids. The granitoids of Petermann Island show no evidence of regional metamorphic alteration under amphibolite facies, which is characteristic of the gabbroids. Therefore, it is assumed that the granitoids were formed after the peak of regional metamorphism in the area. The examination of post-granite diabase dikes indicates that they were intruded at subvolcanic level, after a significant erosion of the enclosing granitoids. The superimposed albite-epidote-chlorite mineralization of postgranite dikes is assumed to be associated with local fracture-controlled low temperature hydrothermal-metasomatic processes.